2003
DOI: 10.1097/00007691-200306000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Phase High-Performance Liquid Chromatography Method for the Analysis of Amprenavir, Efavirenz, Indinavir, Lopinavir, Nelfinavir and Its Active Metabolite (M8), Ritonavir, and Saquinavir in Heparinized Human Plasma

Abstract: The increasing interest in applying therapeutic drug monitoring (TDM) to antiretroviral therapy is related to the observed interindividual variation in antiretroviral pharmacokinetics that results in a wide range of drug exposure from fixed-dosing regimens and the rapid evolution in the availability of phenotypic assays that generate a target 50% inhibitory concentration (e.g., IC(50)) as a basis for adjusting individual antiretroviral dosages. To facilitate the application of TDM, a method for the simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Our present results indicate that both Lopinavir and Ritonavir at concentrations reached in treated patients [32] are able to modulate the cytokine production by PBMCs and macrophages of healthy individuals. We have also shown that the NO-hybridization significantly alters the immunopharmacological profile of Lopinavir but not that of Ritonavir.…”
Section: Resultssupporting
confidence: 50%
“…Our present results indicate that both Lopinavir and Ritonavir at concentrations reached in treated patients [32] are able to modulate the cytokine production by PBMCs and macrophages of healthy individuals. We have also shown that the NO-hybridization significantly alters the immunopharmacological profile of Lopinavir but not that of Ritonavir.…”
Section: Resultssupporting
confidence: 50%
“…Efavirenz and lopinavir concentrations in plasma were measured by high-performance liquid chromatography in the Pharmacology Support Laboratory at the University at Buffalo with methods validated within the Adult AIDS Clinical Trials Group Quality Assurance Proficiency Testing program (18). The lower limits of quantitation were Ͻ100 and Ͻ200 ng/ml for efavirenz and lopinavir, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2.6.2 Atazanavir and ritonavir assays-RTV was quantified using a previously published simultaneous high-performance liquid chromatography (HPLC) assay with slight modification (Keil et al, 2003;Keil et al, in press). ATV was added to this method at a later date following approval.…”
Section: Biochemical Assaysmentioning
confidence: 99%